2021
DOI: 10.22541/au.161980656.66482372/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The phenylpropanoid pathway inhibitor piperonylic acid induces broad-spectrum pest and disease resistance in plants

Abstract: While many phenylpropanoid pathway-derived molecules act as physical and chemical barriers to pests and pathogens, comparatively little is known about their role in regulating plant immunity. To explore this research field, we transiently perturbed the phenylpropanoid pathway through application of the CINNAMIC ACID-4-HYDROXYLASE (C4H) inhibitor piperonylic acid (PA). Using bioassays involving diverse pests and pathogens, we show that transient C4H inhibition triggers systemic, broad-spectrum resistance in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…2A and B ). However, our results are consistent with those obtained by Desmedt and colleagues, who showed that PA-treated plants experience a transient accumulation of ROS that begins within 1 h of treatment ( Desmedt et al 2021 ). The observed increase in ROS molecules ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…2A and B ). However, our results are consistent with those obtained by Desmedt and colleagues, who showed that PA-treated plants experience a transient accumulation of ROS that begins within 1 h of treatment ( Desmedt et al 2021 ). The observed increase in ROS molecules ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Examples of IR stimulants include beneficial microbes such as Trichoderma spp. (Martínez‐Medina et al, 2017 ), natural compounds like piperonylic acid (Desmedt et al, 2021 ) and thiamine (Huang et al, 2016 ), and chemical compounds like the salicylate homologue acibenzolar‐S‐methyl (Romero et al, 2001 ). IR involves both the activation of direct defence responses, where defence pathways are induced, locally or systemically, on contact with the IR stimulus (De Kesel et al, 2021 ), and the so‐called (defence) priming phenomenon, where defence responses are more potently activated on subsequent challenge by stress (Conrath et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated H 2 O 2 levels are associated with resistance of transgenic potato to Erwinia carotovora and Phytophthora infestans (Kuźniak & Urbanek, 2000 ), thiamine IR in rice against M . graminicola (Huang et al, 2016 ), ozonated water IR in tomato against Meloidogyne incognita (Veronico et al, 2017 ), and piperonylic acid IR against pest and diseases in tomato (Desmedt et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…After having shown that DPs are involved in basal immunity against M. graminicola , we wondered whether DPs also contributed to IR against this nematode. We selected two IR stimuli, PA and dehydroascorbic acid (DHA) that had previously shown efficacy against M. graminicola (Singh et al ., 2020; Desmedt et al ., 2021a). We first independently confirmed that both stimuli were indeed effective at inducing systemic resistance in rice ( O. sativa cv Kitaake) seedlings against the rice root‐knot nematode M .…”
Section: Resultsmentioning
confidence: 99%
“…Enhancing rice resistance to M. graminicola through breeding, genetic modification and/or resistance‐inducing chemicals or microbes has been suggested as a key method of sustainable M. graminicola management (Mantelin et al ., 2017). Several resistance‐inducing chemicals have previously proven effective at reducing rice susceptibility to M. graminicola , including piperonylic acid (Desmedt et al ., 2021a), dehydroascorbic acid (Singh et al ., 2020) and β‐aminobutyric acid (Ji et al ., 2015). Induced resistance (IR) refers to a phenomenon in which exposure to a specific exogenous chemical, biotic or abiotic stimulus leads to the induction of a phenotype characterised by enhanced resistance to future biotic (and sometimes abiotic) stresses (Mauch‐Mani et al ., 2017; De Kesel et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%